ANALYSIS OF THE COMPETITIVENESS OF INDONESIAN PROCESSED BLUE SWIMMING CRAB (Portunus pelagicus) IN THE INTERNATIONAL MARKET - Karim, Muhamad; Illahiah, Intan Rohmatul (Universitas Trilogi, 2025)
One of the leading fishery commodities with important economic value is the blue swimming crab (Portunus pelagicus). The product that has a promising market share from this commodity is processed blue swimming crab in the form of cans or airtight packaging which has the HS code 160510. The problem is that the export market share of Indonesian processed crab is limited to certain countries (the United States), while other market shares have not been developed. This study aims to: (i) analyze the competitiveness of Indonesian processed blue swimming crab in the international market, (ii) determine the growth rate of Indonesian processed blue swimming crab exports compared to competing countries, and (iii) formulate a policy strategy to increase the competitiveness of Indonesian processed blue swimming crab in the international market. This study uses time series data and applies the Revealed Comparative Advantage (RCA) and Constant Market Share (CMS) analysis methods. The analysis results show that the average RCA value of Indonesian processed blue swimming crab is 19.86 (RCA> 1) which indicates that Indonesian processed blue swimming crab has a strong comparative advantage in the international market. Indonesia's strategy for increasing the competitiveness and market share of its blue swimming crab exports is developed in two aspects (i) upstream strategy, and (ii) downstream strategy. These two strategies must be supported by traceability implementation policies, digital-based information systems, market intelligence strategies, providing export tax policies for processed crab trade, and complying with regulations in the main export destination countries.